(untitled) - Longoria, Eva; Kilcher, QOrianka; Moner, Isabela; Bobin, James; Toro, Benicio Del; Paramount Home Entertainment (Firm) (Los Angeles, California, 2019)
Having spent most of her life exploring the jungle with her parents, nothing could prepare Dora for her biggest challenge yet: High School. When her parents mysteriously disappear while searching for the Lost City of Gold, Dora must swing into action and lead a group of ill-equipped high schoolers on a quest to save them. It is a high stakes mission as Dora and her new friends navigate the jungle, outrun treasure hunters and solve ancient puzzles to unlock the mystery of the fabled city.
Keywords: the Explorer (Fictitious character); Dora; Juvenile films; Teenagers; Explorers; Drama; Teenagers; Drama; Explorers; Drama; Teenagers; Explorers; Juvenile films; Teenagers; Juvenile films; Explorers; Drama; Childrens films; Feature films; Childrens films; Feature films; Juvenile works